The Impact of Explicit Comprehension Strategy Instruction on First- and Second-Grade At-Risk Students. Issue 3 (October 2019) - Pilonieta, Paola; Hathaway, Jennifer; Medina, Adriana; Casto, Amanda
This study examined the impact of explicit comprehension strategy instruction supported by guided reading and partner reading on at-risk students' strategy knowledge and reading comprehension. Participants were 47 first graders (25 in the treatment group; 22 in the control group) and 44 second graders (19 in the treatment group; 25 in the control group). Treatment group participants developed more specific knowledge of strategies, were more likely to apply those strategies during reading, and demonstrated statistically significant growth in reading comprehension. Strong correlations appeared between students' strategic knowledge and overall comprehension. Implications are addressed at length following the discussion of results.